El uso de drones en España: el ámbito espacial de la ley penal - Ruiz-Morales, Manuel Luis (2018)
The present article analyses various aspects which should be restated because of the widespread usage of drones in the current society, thus as the criminal consequences due to the use of these gadgets. Accordingly, the aim of this writing will be to give possible solutions to the problematic related to commission of crimes because of the use of a drone, paying attention to classical arguments about the criminal law, which is possible to implement. Therefore, a system is collapsible in which it will be preponderated a specific law above another, whereby it always will exist a criminal law applicable to avoid the impunity of the crime committed by a drone.